A soil column model for predicting the interaction between water table and evapotranspiration. Issue 7 (22nd July 2017) - Maquin, Mathilde; Mouche, Emmanuel; Mügler, Claude; Pierret, Marie‐Claire; Viville, Daniel
Abstract: Lateral waterfluxes are not realistically taken into account in soil column models, although they influence the dynamic evolution of the vertical soil moisture profile. By neglecting these fluxes, the modeling of the soil‐vegetation‐atmosphere continuum is incomplete, and the feedbacks between these three compartments cannot be fully simulated. These fluxes have an importance in the different fields where soil column models are used: hydrology, hydrometeorology, biogeochemical cycles, ecology, and soil weathering. This paper introduces a novel Hydrological Hillslope‐based Soil Column model (H2SC) that simulates the temporal evolution of the water table depth and evapotranspiration fluxes and their interaction. The interconnected processes are infiltration, evapotranspiration, vertical soil water movements, and the nonexplicitly modeled lateral fluxes flowing through the soil column. These lateral fluxes are modeled as a drainage function built from physically based equations that describe a simplified hillslope hydrology. This drainage function can be easily implemented in any soil column model without penalizing computational times. The H2SC model was validated on numerical experiments where a 2‐D hillslope simulation performed with an integrated hydrologic model was compared with simulations using the H2SC 1‐D model. Each of the H2SC simulations represents a specific location of a soil column along the hillslope. Different climate forcings, soil properties, and geometric shapes of the hillslope were tested. The model was then applied at the locations of two piezometers in the Strengbach catchment, France. The model reproduced the temporal evolution of the water table level fairly well for both the numerical experiments and for the real test case. Key Points: This paper presents a hillslope‐based column model (1‐D) for modeling the soil‐vegetation‐atmosphere continuum The temporal evolution of the water table depth and its influence on the vegetation is taken into account through a drainage function The results of the model are in good agreement with 2‐D simulations and with piezometers data (Strengbach catchment, France)